(untitled) (Географический вестник=Geographical bulletin, 2017)
Гидрометрическая вертушка сегодня является наиболее развитым и распространенным прибором для измерения скоростей течения в реках и каналах во всем мире. В работе рассматриваются основные тенденции развития гидрометрического приборостроения в странах мира, история появления и развития прибора по направлениям оптимизации его основных компонентов. Выполнены анализ и сопоставление современных гидрометрических вертушек, выпускаемых в мире. К л ю ч е в ы е с л о в а: водный объект; гидрометрия; скорость течения. EVOLUTION OF HYDROMETRIC PROPELLERS IN Russia AND ABROAD Despite of a seeming completeness of development of hydrometric propellers, there are indeterminate problems. To their number refer to: • аbsence of an optimum relationship “sensitivity-componentivity” at which raise of sensitivity of the device would not conduct to an essential decline of componental qualities and on the contrary (the question is solved configuration of a revolving object by several replaceable rotors); • аbsence of a common opinion about agency of relative diameter of the screw and its blade-area ratio on componental properties of the device; • рendency of a question of a trouble-free operation of the device in complex conditions (a frost, the raised mineralization, etc.); • рendency of a question of stability of blade screw parameters for the period of maintenance of the device.